Potentiality of support technologies for opinion and decision-making as a tool for insertion of the geologist in territorial planning - Pedro Benedito Casagrande; Ana Clara Mourão Moura (Disegnare con, 2018)
The Geodesign technique for which it is intended is an alternative exercise plan for a region of the Quadrilátero Ferrífero, in Minas Gerais, Brazil, using a Geology base such as. The geodesy workshop was developed for the mining and construction of a territorial plan for a region. This result is the Decision Model, which is consistent with a study area and has demonstrated that the method used is assertive to landscape and territory planning. DOI: https://doi.org/10.20365/disegnarecon.20.2018.5